2007
DOI: 10.1002/pam.20279
|View full text |Cite
|
Sign up to set email alerts
|

A “politically robust” experimental design for public policy evaluation, with application to the Mexican Universal Health Insurance program

Abstract: We develop an approach to conducting large-scale randomized public policy experiments intended to be more robust to the political interventions that have ruined some or all parts of many similar previous efforts. Our proposed design is insulated from selection bias in some circumstances even if we lose observations; our inferences can still be unbiased even if politics disrupts any two of the three steps in our analytical procedures; and other empirical checks are available to validate the overall de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(125 citation statements)
references
References 52 publications
4
118
1
2
Order By: Relevance
“…This participation represented just 18.5% of 2 Perhaps the most similar study to this one is a recent evaluation by King et al (2009), where the authors evaluated a health insurance program in Mexico that randomized encouragement to sign up for insurance across health facilities. Similar to our study, they measured the shorter term effects (after 10 months) and found a reduction in health expenditures; there were no effects on health outcomes or overall utilization (King et al, 2007(King et al, , 2009. Another study similar to ours evaluated the expansion of government health insurance to the informal sector in Mexico in 2002 (Barros, 2009).…”
Section: Background and Program Descriptionsupporting
confidence: 75%
“…This participation represented just 18.5% of 2 Perhaps the most similar study to this one is a recent evaluation by King et al (2009), where the authors evaluated a health insurance program in Mexico that randomized encouragement to sign up for insurance across health facilities. Similar to our study, they measured the shorter term effects (after 10 months) and found a reduction in health expenditures; there were no effects on health outcomes or overall utilization (King et al, 2007(King et al, , 2009. Another study similar to ours evaluated the expansion of government health insurance to the informal sector in Mexico in 2002 (Barros, 2009).…”
Section: Background and Program Descriptionsupporting
confidence: 75%
“…King et al (2007) However, the program did not show some other expected health effects, possibly due to the short duration of treatment (10 months).…”
Section: Background On Seguro Popularmentioning
confidence: 92%
“…Here, we present an experimental assessment of these health reforms. We introduce aspects of a so called stepped wedge experimental design, 8,9 which uses the phased rollout of the national programme to make randomisation politically feasible and ethical. We also discuss expectations, including the idea that Seguro Popular funds would reach the poor and increase health-care utilisation.…”
Section: Introductionmentioning
confidence: 99%